2022
DOI: 10.1177/13694332221088945
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing effect of polyurea resin coating on RC members subject to low-speed and medium-speed impact

Abstract: Polyurea resin is widely used as a coating material for various structures owing to its relatively high strength and elongation ability along with applicability in improving the impact and explosion resistance of structures has been studied. Civil engineering structures are generally subjected to relatively low-speed impact loads, such as collisions with vehicles, falling rocks, and flying objects caused by typhoons. However, the reinforcing effect of polyurea resin against low-speed impact loads has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was also found that polyurea can hardly improve the static load carrying capacity of reinforced concrete arches in the study by Liu et al [40]. Notably, in the study by Sonoda et al [114], they revealed that the polyurea protective coating is also not effective against RC structures for the first impact loading action at low and medium strain rates. With repeated impacts, however, the improvement of polyurea on the impact resistance of RC structures is significant and can significantly inhibit structural cracking and rigidity loss [114].…”
Section: Protection Of Civil Engineering Structuresmentioning
confidence: 95%
See 1 more Smart Citation
“…It was also found that polyurea can hardly improve the static load carrying capacity of reinforced concrete arches in the study by Liu et al [40]. Notably, in the study by Sonoda et al [114], they revealed that the polyurea protective coating is also not effective against RC structures for the first impact loading action at low and medium strain rates. With repeated impacts, however, the improvement of polyurea on the impact resistance of RC structures is significant and can significantly inhibit structural cracking and rigidity loss [114].…”
Section: Protection Of Civil Engineering Structuresmentioning
confidence: 95%
“…Notably, in the study by Sonoda et al [114], they revealed that the polyurea protective coating is also not effective against RC structures for the first impact loading action at low and medium strain rates. With repeated impacts, however, the improvement of polyurea on the impact resistance of RC structures is significant and can significantly inhibit structural cracking and rigidity loss [114]. Among the many researchers studying the polyurea enhancement of concrete structures against blast and impact loads, the polyurea inhibition of structural crack evolution and spalling is considered an important macroscopic level of protection.…”
Section: Protection Of Civil Engineering Structuresmentioning
confidence: 99%